Antiproliferative effect of alkaloids via cell cycle arrest from Pseuduvaria rugosa - Uadkla O. (2014)
Context: Pseuduvaria rugosa (Blume) Merr. (Annonacaea) grows widely in the south and southeast regions of Thailand. Preliminary screening for biological activities revealed that crude hexane, ethyl acetate, and acetone extracts from mixtures of leaves and twigs of P. rugosa showed cytotoxicity. Objective: Chemical constituents and their antiproliferative activity in K562, U937, and HL-60 human leukemic cell lines from P. rugosa were performed for the first time. Materials and methods: The isolated compounds were obtained from chromatographic separation. The structures were established by spectroscopic techniques including IR, UV, NMR together with 2D NMR (HMBC, COSY, and NOE) and MS. The K562, U937, and HL-60 cell lines were treated with isolated aporphine alkaloids (0-100g/mL) and cell viability was measured with the MTT assay. Cell cycle analysis was performed using propidium iodide (PI) based staining methods. Results: Two known aporphine alkaloids, 1,2,3-trimethoxy-5-oxonoraporphine (1) and ouregidione (2) were isolated. Treatment of the cells with compounds 1 and 2 at a concentration of 100 g/mL for 72h reduced the viability of K562, U937, and HL-60 cell lines to 63 and 64, 38 and 66, and 49 and 64%, respectively. In addition, compounds 1 and 2, at a concentration of 100g/mL, exposed to U937 and HL-60 cell lines showed cell cycle arrest. The U937 cell line treated with compounds 1 and 2 increased significantly the proportion of the cell in S phase, whereas the HL-60 cell line-induced G2/M and G1 phase, respectively. Discussion and conclusion: The results showed that 1,2,3-trimethoxy-5-oxonoraporphine and ouregidione-induced cytotoxicity with HL-60, U937, and K562 cells where 1,2,3-trimethoxy-5-oxonoraporphine was more active than ouregidione. © 2013 Informa Healthcare USA, Inc.